Exploring revenue trends in alley commercial areas in Seoul, Korea - Hongjai Rhee (KDI Journal of Economic Policy, 2024)
This study examines changes in sales by business category and area in Korea's small commercial districts. Unlike previous studies that focused primarily on overall sales levels before and after the COVID-19 pandemic, this paper emphasizes temporal variations in the inequality of sales distributions. Using credit-card-based data comprising 392,832 sales records aggregated by (category, area) units, the primary analysis reveals that sales distributions have recently become more dispersed across most categories, underscoring the vulnerability of less-advantaged areas in the post-pandemic period. In a secondary analysis, regression and machine learning models were applied to investigate factors influencing regional sales disparities. The findings indicate that although overall sales, which declined sharply during the pandemic, rebounded rapidly after 2021, they have shown a significant downturn in recent periods. The paper concludes with a discussion of relevant policy implications.
Keywords: L1; L8; C5; 330; Commercial Districts; Sales Growth; Distributional Inequality; COVID-19